Neurovascular injury in acute knee dislocation: evaluation of an algorithm for selective arteriography. Issue 5 (September 2016) - Roberson, Troy A.; Throckmorton, Thomas W.; Miller, Robert H.; Smith, Richard A.; Azar, Frederick M.
Abstract : Background: The role of arteriography in acute knee dislocations has evolved from routine use to most authors advocating selective arteriography. Further refining and education are necessary to identify patients at increased risk of popliteal artery injury and avoid missing serious injuries while at the same time avoiding unnecessary arteriography. Our hypothesis was that selective arteriography algorithm would identify all flow-limiting popliteal artery injuries, and patients with a body mass index (BMI) over 40 will have higher rates of popliteal artery and peroneal nerve injuries than nonobese patients. Methods: Fifty-three patients treated for an acute knee dislocation over a 5-year period (2007-2012) were included. Patients with a normal neurovascular examination or ankle-brachial indices (ABI) greater than 0.9 were clinically observed. Those with abnormal ABI (<0.9) but palpable pulses had an arteriogram at the discretion of the attending physician, while patients with pulse discrepancy compared to the contralateral side had arteriography. Missed injuries were defined as worsening clinical examination resulting in further diagnostic evidence of vascular injury prior to discharge. Results: The rate of popliteal artery injury was 17% (9 of 53) and peroneal nerve injury 38% (20 of 53). There were no missed vascular injuries using the selective arteriography algorithm. Morbid obesity (BMI>40) was significantly associated with popliteal artery injury and the mean BMI was significantly higher (40 vs. 33) in patients with popliteal artery injury. Time to reduction of more than 6 hr trended toward association with popliteal artery injury while transfer from another facility was not significant. Falls from a standing height were not significantly associated with popliteal artery injury, while peroneal nerve injury was significantly higher with this ultra-low-velocity mechanism. Conclusions: There were no missed vascular injuries with the use of a selective arteriography algorithm. Morbid obesity and an ultra-low-velocity mechanism were associated with an increased risk of neurovascular injury in acute knee dislocations, but arteriography was not found to be mandatory in this population.